Development of Domestic Refrigerator Trainer: An Instructional Material for Beginner Technician - Bajet, Jr., Manuel A.; Bajet, Nelson (JPAIR Multidisciplinary Research, 2014)
The University of Northern Philippines is one arm of the government in developing skilled manpower. It envisioned produce highly skilled graduates employed in the country and abroad to boost the country’s economy and support themselves and their families. The objectives can only be realized if it is properly equipped with laboratory facilities that can provide hands-on training for students. The Technology Department has been facing problems of inadequate instructional materials and facilities, especially those that could help in the development of the student’s manipulative skills. The design and development domestic refrigerator trainer used locally available materials. The conceptualization of the trainer is in the intellectual capability of refrigeration and air conditioning faculty researchers. The domestic refrigerator trainer in its advancement in the teaching and learning process is and the principle operations, easy to understand the different connection of electric circuitry in the mechanical components. The trainer can also present the four phases of refrigerant cycle .Its design focuses on skills training approach to aid the beginner student in an easy and comprehensive way of learning the trade in a very limited time that servicing and repair is in his hands.